Pengujian Black Box pada Sistem Aplikasi Informasi Data Kinerja Menggunakan Teknik Equivalence Partitions - Andri Ricat Sinulingga; Muhammad Zuhri; Rizky Budi Mukti; Zia Syifa; Aries Saifudin (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Software that contains defects (errors) can cause harm. Losses caused can affect all stakeholders. Losses can take the form of financial, time, and others. So before the software is implemented it needs to be tested. Testing on an application aims to check whether a program is running properly or not. In testing this software will use Blackbox Testing. Black Box Testing Method consists of several techniques, including Equivalence Partitions, Boundary Value Analysis, Sample Testing, and so on. Among the many testing techniques, in this study the testing technique was chosen using Equivalence Partitions. Equivalence Partitions technique is a test based on data input on each form in the performance data information application system, each menu input will be tested and grouped according to function whether it is valid or invalid. Testing is done on 4 forms that will be filled with data form added jobdesk, form added work targets, form edit work targets, form approve work targets, and employee performance while in the company. The test results show that there are still many shortcomings when validating data to be entered, so that it can cause data stored in the database to be incompatible with the expected data. The results of this test can be used as input to improve the application of performance data for the future.